ANALISIS PENILAIAN HARGA WAJAR SAHAM MENGGUNAKAN PENDEKATAN DIVIDEND DISCOUNT MODEL, PRICE EARNING RATIO DAN PRICE TO BOOK VALUE - Ismunarti, Nurbani Aulia; Sunarko, Bambang; Tohir, Tohir (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
The purpose of this research is to determine the intrinsic value of coal mining company stock listed in LQ45 Index during 2010-2014 period used Dividend Discount Model (DDM) Pertumbuhan Berganda, Price Earning Ratio (PER) and Price to Book Value (PBV) approach. Intrinsic value will compared with market stock value, henceforth be one of basic for taking investment decision in capial market. Difference of intrinsic stock value with market stock value is tasted by Paired Sample T-Test. For this research, the sample used is PT. Adaro Energy Tbk (ADRO), PT. Indo Tambangraya Megah Tbk (ITMG) and PT. Bukit Asam Tbk (PTBA).The result of this research showed that the market stock value of the coal mining company listed in LQ45 Index is higher than intrinsic stock value (overvalued) based DDM Pertumbuhan Berganda and PBV approach. While based PER approach, the market stock value of the coal mining company is lower than intrinsic stock value (undervalued). And then, for the result of paired sample t-test showed that based on DDM Pertumbuhan Berganda , PER and PBV approach has a significant difference between intrinsic value with market stock value.